2009
DOI: 10.1038/ejcn.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex and ethnic differences in the prevalence of underweight and overweight, defined by using the CDC and IOTF cut points in Asian children

Abstract: Background: No nationally representative data from middle-and low-income countries have been analyzed to compare the prevalence of underweight and overweight, defined by using the Centers for Disease Control and Prevention (CDC) and the International Obesity TaskForce (IOTF) body mass index cut points. Objective: To examine the consistency in the prevalence of underweight and overweight, defined by using the CDC and IOTF cut points in Chinese, Indonesian and Vietnamese children. Methods: We used data from 1600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
4
24
0
4
Order By: Relevance
“…Although the prevalence of overweight and obesity is receiving considerable attention in terms of both policy and practice in China, however, our study suggests that thinness is also an important overlooked phenomenon. As suggested by findings of previous studies from other developing countries [7][8][9][10], our results indicated that China is facing the double burden of both thinness and overweight. Therefore, it is important not to forget the public health challenge posed by thinness.…”
supporting
confidence: 77%
“…Although the prevalence of overweight and obesity is receiving considerable attention in terms of both policy and practice in China, however, our study suggests that thinness is also an important overlooked phenomenon. As suggested by findings of previous studies from other developing countries [7][8][9][10], our results indicated that China is facing the double burden of both thinness and overweight. Therefore, it is important not to forget the public health challenge posed by thinness.…”
supporting
confidence: 77%
“…Previous researchers have indicated that because these growth charts were developed using different populations for different purposes, they use different cut‐offs for adiposity and thus yield different prevalences. This has been reported in countries such as Canada (Shields & Tremblay, 2010), China (Tuan & Nicklas, 2009), and Korea (Khang & Park, 2011).…”
Section: Selecting the Appropriate Bmi Chart To Assess Adiposity Of Smentioning
confidence: 70%
“…Lang, Kipping, Jago, and Lawlor (2011) found a 1.2% to 1.4% difference between these two standards in overweight/obesity prevalence in 12-to 17-year-old U.S. and English adolescents. In a sample of Asian children, differences between absolute agreement of overweight/obesity prevalence using the IOTF and Fitnessgram standards were within 2% (Tuan & Nicklas, 2009). Like the aforementioned studies, the difference between the standards' combined prevalence of overweight/obesity was approximately 2%.…”
Section: Discussionmentioning
confidence: 92%